Assessing Informal Employment and Skills Needs: Approaches and Insights from Regional and Local Labour Market Monitoring - Larsen, Christa; Rand, Sigrid; Schmid, Alfons; Bobkov, Vyacheslav; Lokosov, Vyacheslav (Rainer Hampp Verlag, 2019)
The scope of informal economy and the forms of informal employment differ greatly between countries. Therefore, studying the role of informal employment in the labour market from a comparative perspective provides important insights into economic and social developments in regions and localities. The present publication discusses various concepts and definitions for capturing and analysing informal employment. Furthermore, it demonstrates how a broad variety of methods can be applied for conducting research on informal employment and explores the available data sources. Besides presenting innovative conceptual and methodological approaches towards analysing informal employment, the Anthology of the European Network on Regional Labour Market Monitoring (EN RLMM) discusses how these insights can be used for developing the Network’s concept for regional and local labour market monitoring (RLMM) further